Innovations in surgical management of nonobstructive azoospermia - Ran, Renzhong (Indian J Urol, 2016)
Testicular sperm extraction (TESE) technique and intra-cytoplasmic sperm injection are breakthrough fertility treatments for men with nonobstructive azoospermia (NOA). Newer advances such as the microdissection-TESE (micro-TESE) technique have continued to build upon past success by improving sperm retrieval and minimizing the postoperative complications compared to TESE. However, even with micro-TESE, sperm retrieval success has ranged from 40% to 60% due to the technique's dependence on surgeon and embryologist experience. While postoperative complications are minimal relative to the traditional TESE technique, testicular tissue must still be extracted without the knowledge of whether sperm are present in biopsies. In this review, we discuss the innovations in the surgical management of men with NOA and describe the novel experimental approaches that can improve sperm retrieval success.